2019
DOI: 10.1136/ijgc-2018-000073
|View full text |Cite
|
Sign up to set email alerts
|

Cardiophrenic lymph node resection in cytoreduction for primary advanced or recurrent epithelial ovarian carcinoma: a cohort study

Abstract: ObjectivesTo evaluate the clinical outcomes of epithelial ovarian carcinoma patients who underwent cardiophrenic lymph node resection.MethodsWe retrospectively reviewed the records of all surgically treated patients with advanced epithelial ovarian carcinoma (stages IIIC–IV) who underwent cardiophrenic lymph node resection between 2002 and 2018. Only those in whom cardiophrenic lymph node involvement was the only detectable extra-abdominal disease were included. Patients with suspected cardiophrenic lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Surgical resection of these nodes via the transdiaphragmatic approach has become common at some institutions. This has been shown to be both feasible and safe, with a marginal increase in operating time and short-term morbidity 5 7 12–14. Initial long-term data have suggested that surgical resection has little role in extending survival, but has not identified the effect of this practice on sites of recurrence utilizing a comparison group 8…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection of these nodes via the transdiaphragmatic approach has become common at some institutions. This has been shown to be both feasible and safe, with a marginal increase in operating time and short-term morbidity 5 7 12–14. Initial long-term data have suggested that surgical resection has little role in extending survival, but has not identified the effect of this practice on sites of recurrence utilizing a comparison group 8…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen articles described retrospective cohort studies [ 9 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], one was a case report [ 34 ], and one a case series [ 35 ]. The studies spanned the period from 1997 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this finding, only a slightly higher proportion of perioperative complications was found for the CPLN adenopathy group (26% vs. 23%). Eight studies provided survival outcomes [ 9 , 11 , 24 , 25 , 26 , 29 , 32 , 33 ]. The pooled median PFS time was 14.6 months (95% CI 4.9–24.4) vs. 27.8 months (95% CI 3.2–52.5) in patients with and without CPLN adenopathy, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations